Low-Frequency Electroacupuncture Improves Insulin Sensitivity in Obese Diabetic Mice through Activation of SIRT1/PGC-1α in Skeletal Muscle. (26th September 2010) - Liang, Fengxia; Chen, Rui; Nakagawa, Atsushi; Nishizawa, Makoto; Tsuda, Shinichi; Wang, Hua; Koya, Daisuke
Abstract : Electroacupuncture (EA) has been observed to reduce insulin resistance in obesity and diabetes. However, the biochemical mechanism underlying this effect remains unclear. This study investigated the effects of low-frequency EA on metabolic action in genetically obese and type 2 diabetic db/db mice. Nine-week-old db/m and db/db mice were randomly divided into four groups, namely, db/m, db/m + EA, db/db, and db/db + EA. db/m + EA and db/db + EA mice received 3-Hz electroacupuncture five times weekly for eight consecutive weeks. In db/db mice, EA tempered the increase in fasting blood glucose, food intake, and body mass and maintained insulin levels. In EA-treated db/db mice, improved insulin sensitivity was established through intraperitoneal insulin tolerance test. EA was likewise observed to decrease free fatty acid levels in db/db mice; it increased protein expression in skeletal muscle Sirtuin 1 (SIRT1) and induced gene expression of peroxisome proliferator-activated receptorγ coactivator1 α (PGC-1 α ), nuclear respiratory factor 1 (NRF1), and acyl-CoA oxidase (ACOX). These results indicated that EA offers a beneficial effect on insulin resistance in obese and diabetic db/db mice, at least partly, via stimulation of SIRT1/PGC-1 α, thus resulting in improved insulin signal.